Pelatihan Pemanfaatan Limbah Rumah Tangga Menjadi Pakan Ternak Kaya Protein - Dedi Holden Simbolon; Eka Kartika Silalahi; Joen Parningotan Purba; Theresia Perbina; Alena Rosiana Manik (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Household waste is one of the major contributors to environmental problems in densely populated areas, including Kenangan Village in Percut Sei Tuan District. Limited waste management systems have led to the accumulation of organic waste, environmental pollution, and declining public health. At the same time, the rising cost of commercial animal feed has become an economic burden for low-income families. This community service program aims to provide an integrated solution through training on Black Soldier Fly (BSF) larvae cultivation to convert organic waste into animal feed and organic fertilizer. The implementation methods included lectures, discussions, demonstrations, hands-on practice, and field mentoring. The results indicate an improvement in the community’s understanding of organic waste processing, significant reduction of organic waste volume, and the production of maggot culture as livestock feed and organic fertilizer. In addition, participants were motivated to initiate small businesses based on maggot production and its residue. This program has proven to be effective as a circular economy solution that integrates waste management, household economic improvement, and community empowerment. The activity is recommended for broader and continuous implementation.